PENERAPAN STRATEGI BELAJAR AKTIF TIPE INDEX CARD MACTH UNTUK MENINGKATKAN MOTIVASI BELAJAR PKn SISWA KELAS III SD NEGERI 13 KERINCI KANAN KABUPATEN SIAK - Supriadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low Civics learning outcomes of third-grade students at SD Negeri 13 Kerinci Kanan, Siak. The study aimed to examine the improvement of Civics learning outcomes through the application of the Index Card Match method among third-grade students at SD Negeri 13 Kerinci Kanan, Siak. The research was conducted over a period of one month. The subjects of this study were six third-grade students in the 2015–2016 academic year, consisting of five male students and one female student. The research employed a classroom action research design. The research instruments included performance instruments and data collection tools in the form of teacher and student activity observation sheets. Based on the results and discussion, the implementation of active learning strategies using the Index Card Match type was proven to enhance students’ learning motivation. Teacher activity in Cycle I achieved a score of 36, categorized as good, while in Cycle II it increased to a score of 44, categorized as very good. Student learning motivation in Cycle I obtained an average score of 52.8, classified as high, and increased significantly in Cycle II with an average score of 80.6, also categorized as high. In Cycle I, the classroom action research had not yet achieved the expected success indicators; however, in Cycle II, the research was considered successful as the achievement indicator of 75.0% was exceeded. These findings indicate that the application of active learning strategies using the Index Card Match method is effective in increasing motivation to learn Civics among third-grade students at SD Negeri 13 Kerinci Kanan, Siak.